Rules of benefit distribution: A dynamic impact on Nepalese community forestry organizations. (17th February 2017) - Yadav, Bhagwan Dutta; Bigsby, Hugh; MacDonald, Ian
ABSTRACT: Participatory approach has been an official part of Community Forestry (CF) since 1989 when Master Plan for the Forestry Sector (1989) was introduced in Nepal. However, many problems related to benefit distribution from CF have emerged because of the way decision-making is influenced by social and institutional structures present at community level, particularly in terms of dominance by wealthy and caste elite to formulate rules. The study used a conceptual approach using elite theory with models that looked at Executive Committee (EC) that used to formulate distribution rules. The study uses Community Forestry User Groups (CFUGs) level data from 31 CFUGs and household data from 310 households in Baglung district, Nepal. The study examined the factors linked with rules of distribution that determined the relative distribution of forest products. The higher the representation of the poor and disadvantaged households on the EC, the greater the benefits to them in terms of greater quantities distributed and longer collection periods. The policy implication of this study is that the forestry organizations help the poor and underprivileged households to build up capacity to undertake leadership roles that influence the formulation of rules through which organizational elite models in favor to them become part of the elite decision-making.